Risk Factors for Reoperation and Performance-based Outcomes following Surgical Fixation of Foot Fractures in the Professional Athlete: A Cross-Sport Analysis. Issue 7 (21st July 2017) - Singh, Sameer Kumar; Larkin, Kevin; Kadakia, Anish R.; Hsu, Wellington
Objectives: Professional athletes are predisposed to fractures of the foot due to large stresses placed on the lower extremity; these players are concerned with efficiently returning to play at a high level. Return to play rates following operative treatment have been previously reported, yet performance outcomes following such treatment are generally unknown in this population. The purpose of this study was to assess and compare performance-based outcomes following foot fracture fixation among professional athletes of the 4 major North American sports. Methods: Athletes in the National Basketball League (NBA), National Football League (NFL), (Major League Baseball) MLB, and National Hockey League (NHL) undergoing operative fixation of a foot fracture were identified through a well-established protocol confirmed by multiple sources of the public record. Return-to-play rate and time to return were collected for each sport. League participation and game performance were collected before and after surgery. Statistical analysis was performed with significance accepted as P ≤ .05. Results: A total of 77 players undergoing 84 procedures met the inclusion criteria. Overall, 98.7% of players were able to return to play with an average time to return across all sports of 172 ± 22 days. Players returned to preoperative performance levels within one season of surgery. Six players (7.8%) sustained re-fracture requiring reoperation, all of whom were in the NBA. Percentage of games started during the season after primary surgical treatment was a predictive factor for re-injury (99% vs 40%, p = .001). Conclusion: Athletes returned to play following foot fracture fixation at a high rate with excellent postoperative performance levels, regardless of sport and fracture location. NBA athletes sustaining fifth metatarsal and navicular fractures are at a higher risk of re-injury compared to other athletes. Returning to high levels of athletic participation soon after surgery may predispose athletes to re-fracture and subsequent reoperation.